Implikasi Atas Berlakunya Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII-2015 terhadap Perjanjian Perkawinan di Indonesia - Matina Candra, Ingrid Fransisca; Aidi, Zil (UNES Law Review, 2024)
This research discusses the making of a marriage agreement before and after the marriage period in terms of Indonesian law. The purpose of this research is to understand the differences in the application of marital agreements made before and after the issuance of the Constitutional Court Decision Number 69/PUU-XIII-2015. This research uses a normative juridical method by examining several laws and regulations governing marital agreements. The results of this study indicate that the making of a marriage agreement during the marriage period is a valid agreement because the Constitutional Court Decision Number 69/PUU-XIII-2015 regarding the timing of making a marriage agreement is a final and binding decision.